2012
DOI: 10.1192/bjp.bp.111.101543
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of psychotic experiences in non-psychotic young people: evidence from four population-based studies

Abstract: Hallucinations and delusions, the classic symptoms of psychosis, have recently been documented to occur at a much higher prevalence in the general population than clinically diagnosed psychotic disorder.1 A meta-analysis of prevalence studies of psychotic symptoms in young people demonstrated a median prevalence of 17% in children aged 9-12 years and 7.5% in adolescents aged 13-18 years.2 As the term suggests, psychotic symptoms have typically been considered to relate to psychotic disorder. Indeed, research h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
410
5
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 408 publications
(467 citation statements)
references
References 47 publications
42
410
5
1
Order By: Relevance
“…However, more research on underlying mechanisms is 13 required. The results of the present study show that PE serve as an indicator of illness severity and poor outcome in persons with non-psychotic psychopathology, in line with previous research (Guloksuz et al, 2015;Kelleher et al, 2012b;Perlis et al, 2011;Wigman et al, 2012;Wigman et al, 2014). Therefore, assessment of PE in individuals with non-psychotic psychopathology should be incorporated both in clinical practice and in future research, as previously suggested (Kelleher et al, 2013), in order to identify individuals at risk of suicidal behaviour.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…However, more research on underlying mechanisms is 13 required. The results of the present study show that PE serve as an indicator of illness severity and poor outcome in persons with non-psychotic psychopathology, in line with previous research (Guloksuz et al, 2015;Kelleher et al, 2012b;Perlis et al, 2011;Wigman et al, 2012;Wigman et al, 2014). Therefore, assessment of PE in individuals with non-psychotic psychopathology should be incorporated both in clinical practice and in future research, as previously suggested (Kelleher et al, 2013), in order to identify individuals at risk of suicidal behaviour.…”
Section: Discussionsupporting
confidence: 89%
“…It remains unclear, however, how to isolate this specific association from the association between non-psychotic psychopathology and suicidal ideation and behaviour, since non-psychotic psychopathology is strongly connected to both PE (DeVylder et al, 2014;Guloksuz et al, 2015;Jeppesen et al, 2015;Kelleher et al, 2012b;Van Os et al, 2000), and suicidal behaviour (Cavanagh et al, 2003;ten Have et al, 2009;Ten Have et al, 2013). Suicidality comprises various phenomena on a continuum ranging from suicidal ideation, suicide plans and suicide attempts to completed suicide (Nock, 2010;Sveticic and De Leo, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations